Resident burnout in USA and European urology residents: an international concern. (8th May 2019) - Marchalik, Daniel; C. Goldman, Charlotte; F. L. Carvalho, Filipe; Talso, Michele; H. Lynch, John; Esperto, Francesco; Pradere, Benjamin; Van Besien, Jeroen; E. Krasnow, Ross
Abstract : Objective: To describe the prevalence and predictors of burnout in USA and European urology residents, as although the rate of burnout in urologists is high and associated with severe negative sequelae, the extent and predictors of burnout in urology trainees remains poorly understood. Subjects and methods: An anonymous 32‐question survey of urology trainees across the USA and four European countries, analysing personal, programme, and institutional factors, was conducted. Burnout was assessed using the validated abridged Maslach Burnout Inventory. Univariate analysis and multivariable logistic regression models assessed drivers of burnout in the two cohorts. Results: Overall, 40% of participants met the criteria for burnout as follows: Portugal (68%), Italy (49%), USA (38%), Belgium (36%), and France (26%). Response rates were: USA, 20.9%; Italy, 45.2%; Portugal, 30.5%; France, 12.5%; and Belgium, 9.4%. Burnout was not associated with gender or level of training. In both cohorts, work–life balance (WLB) dissatisfaction was associated with increased burnout (odds ratio [OR] 4.5, P < 0.001), whilst non‐medical reading (OR 0.6, P = 0.001) and structured mentorship (OR 0.4, P = 0.002) were associated with decreased burnout risk. Lack of access to mental health services was associated with burnout in the USA only (OR 3.5, P = 0.006), whilst more weekends on‐call was associated with burnout in Europe only (OR 8.3, P = 0.033). In both cohorts, burned out residents were more likely to not choose a career in urology again (USA 54% vs 19%, P < 0.001; Europe 43% vs 25%, P = 0.047). Conclusion: In this study of USA and European urology residents, we found high rates of burnout on both continents. Despite regional differences in the predictors of burnout, awareness of the unique institutional drivers may help inform directions of future interventions.